2005
DOI: 10.1128/jb.187.10.3293-3301.2005
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and Growth of Shewanella oneidensis MR-1 Using Vanadate as the Sole Electron Acceptor

Abstract: Shewanella oneidensis MR-1 is a free-living gram-negative ␥-proteobacterium that is able to use a large number of oxidizing molecules, including fumarate, nitrate, dimethyl sulfoxide, trimethylamine N-oxide, nitrite, and insoluble iron and manganese oxides, to drive anaerobic respiration. Here we show that S. oneidensis MR-1 is able to grow on vanadate as the sole electron acceptor. Oxidant pulse experiments demonstrated that proton translocation across the cytoplasmic membrane occurs during vanadate reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 46 publications
4
67
0
Order By: Relevance
“…The Fe(II) production was confirmed by a separate experiment, which was performed by adding K 4 [Fe(CN) 6 ] or K 3 [Fe(CN) 6 ] to the microbe-Fe(III) medium before starting the incubation (Fig. S5).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The Fe(II) production was confirmed by a separate experiment, which was performed by adding K 4 [Fe(CN) 6 ] or K 3 [Fe(CN) 6 ] to the microbe-Fe(III) medium before starting the incubation (Fig. S5).…”
Section: Resultsmentioning
confidence: 90%
“…4 Shewanella oneidensis MR-1 is a facultative anaerobe that can use a variety of inorganic and organic compounds as terminal electron acceptors for anaerobic respiration, and has been often referred to as dissimilatory metal-reducing bacteria; the acceptors that have been listed include Fe(III), U(VI), Mn(IV), V(V), nitrate, dimethyl sulfoxide, and fumarate. [5][6][7] Currently, the growing interest in this species is to a large extent directed toward potential applications in biotechnology, such as remediation of soils and aquifers that have been contaminated with heavy metals or radionuclides, and a biocatalyst in microbial fuel cells. [7][8][9][10][11][12] S. oneidensis can grow not only aerobically, but also anaerobically with a variety of organic and inorganic substances as the terminal electron acceptor.…”
mentioning
confidence: 99%
“…Under this conditions, other electron acceptors such as nitrate or metal ions such as manganese or iron would be used as an alternative (Haley et al, 2012). Resting cells have been used in studying heavy metals reduction such as in selenate (Losi and Jr, 1997), vanadate (Carpentier et al, 2005), chromate (Llovera et al, 1993), reductions and xenobiotics biodegradation such as phenol (Sedighi and Vahabzadeh, 2014), amides (Raj et al, 2010), diesel (Auffret et al, 2015), SDS (Chaturvedi and Kumar, 2011), and pentachlorophenol (Steiert et al, 1987).…”
Section: Identification Of Molybdenum-reducing Bacteriummentioning
confidence: 99%
“…Since Cr(III) compounds are relatively solureduction of Cr(VI) have been reported (Suzuki et al, ble only under very acidic or very basic conditions (Rai 1992;Myers et al, 2000;Neal et al, 2002;Kalabegishvili et al, 1987Kalabegishvili et al, , 1989 and their soluble organo complexes et al., 2003). Electron paramagnetic resonance (EPR) mea- (Puzon et al, 2005) are large molecules that are not easily surements, sensitive to non-integer spin transition metals transported across the outer membrane, bacteria with memsuch as Cr(I), Cr(III), and Cr(V), suggested that Cr(V) is brane-bound reductases are constrained to reduce Cr(VI) to a possible redox intermediate for Cr(VI) reduction by PseuCr(III) by extracellular processes (e.g., see Wang et al, domonas ambigua (G-1) (Suzuki et al, 1992), Arthrobacter 1990), e.g., by using electron-shuttling compounds coupled oxydans (Kalabegishvili et al, 2003), and Shewanella oneidto membrane reductases. Otherwise a mechanism of Cr(Ill) ensis (Myers et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2). (S032-), thiosulfate (S2032-), tetrathionate (S4062-), fumarate, glycine, and trimethylamine N-oxide (see Myers and 2.2 Nealson, 1988a,b;Lovley et al, 1991;Llyod and Macaskie, 1996;Carpentier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%